Skull Metastasis From Uterine Leiomyosarcoma, a Rare Presentation for a Rare Tumor: A Case Report and Review of the Literature - Rizzo, Alessandro; Nigro, Maria Concetta; Ramponi, Vania; Gallo, Carmine; Perrone, Anna Myriam; De Iaco, Pierandrea; Frezza, Giovanni; Balestrini, Damiano; Di Benedetto, Maika; Morbiducci, Jarno; Pantaleo, Maria Abbondanza; Nannini, Margherita (Frontiers in Oncology, 2020)
Uterine leiomyosarcoma (uLMS) is a rare and aggressive malignancy with poor clinical outcomes. Even when localized, uLMS is associated with high rates of local and distant recurrences that are usually fatal. Common sites of recurrence are lung, liver, pelvic lymph nodes, vertebral and long bones although atypical patterns of recurrence have been described. Among them, intracranial recurrence appears as a rare finding, almost exceptional in skull and dura. Herein, we describe the case of a solitary skull metastasis from uLMS in a 39-year-old woman, which represents the third reported case of skull recurrence in literature. After multidisciplinary discussion, the patient underwent surgery and received adjuvant radiotherapy. After 4 months, she is currently alive, without evidence of extracranial disease. This case highlights the importance of suspecting and recognizing atypical and extremely rare metastasis to this region. We encourage the need for large case series in order to provide further information about cranial recurrences of uLMS taking into account the paucity of data currently available in literature and the frequently unpredictable behavior of this rare, highly lethal, disease.